Pilot Feasibility Study of A Digital Storytelling Intervention for Immigrant and Refugee Adults with Diabetes - Wieland, Mark L. (Diabetes Educ, 2017)
PURPOSE: The purpose of this pilot feasibility project was to examine the potential effectiveness of a digital storytelling intervention designed through a community-based participatory research approach for immigrants and refugees with type 2 diabetes mellitus (T2DM). METHODS: The intervention was a 12-minute culturally and linguistically tailored video consisting of an introduction, 4 stories, and a concluding educational message. A structured interview was used to assess the intervention for acceptability, interest level, and usefulness among 25 participants with T2DM (15 Latino, 10 Somali) across 5 primary care clinical sites. After watching the video, participants rated their confidence and motivation about managing T2DM as a result of the intervention. Baseline hemoglobin A(1c) (A1C) and follow-up values (up to 6 months) were abstracted from medical records. RESULTS: All participants reported that the intervention got their attention, was interesting, and was useful; 96% reported that they were more confident about managing their T2DM than before they watched the video; and 92% reported that the video motivated them to change a specific behavior related to T2DM self-management. The mean baseline A1C level for the intervention participants was 9.3% (78 mmol/mol). The change from baseline to first follow-up A1C level was −0.8% (−10 mmol/mol) (P<.05). CONCLUSIONS: Implementation of a digital storytelling intervention for T2DM among immigrant populations in primary care settings is feasible and resulted in self-rated improvement in psychosocial constructs that are associated with healthy T2DM self-management behaviors, and there was some evidence of improvement in glycemic control. A large-scale efficacy trial of the intervention is warranted.